Organic sensors materials and applications - García Breijo, Eduardo; Pérez, Berta Gómez-Lor; Cosseddu, Piero (IET control, robotics and sensors series, 2016)
This book reviews the state of the art in the use of organic materals as physical, chemical and biomedical sensors in a variety of application settings. Topics covered include organic semiconductors for chemical and physical sensing; conducting polymers in sensor applications; chemically functionalized organic semiconductors for highly selective sensing; composite organic-inorganic sensors; artificial skin applications; organic thin film transistor strain gauges for biomedical applications; OTFT infrared sensors for touchless human-machine interaction; smart fabric sensors and e-textile technologie; image capture with organic sensors; organic gas sensors and electronic noses; electrolyte gated organic transistors for bio-chemical sensing; ion-selective organic electrochemical transistors; DNA biosensors; metabolic organic sensors; and conductive polymer based sensors for biomedical applications